أثر المسؤولية المجتمعية في تحسين السمعة التنظيمية بوجود المعمارية التنظيمية كمتغير معدل في البنوك التجارية الأردنية - Alhjaya, Nasser Nawaf; Abu Hussein, Alhareth (جامعة العلوم التطبيقية الخاصة - عمادة البحث العلمي والدراسات العليا, 2023)
هدفت الدراسة إلى التعرف على أثر المسؤولية المجتمعية في تحسين السمعة التنظيمية بوجود المعمارية التنظيمية كمتغير معدل في البنوك التجارية الأردنية، تكون مجتمع الدراسة من المديرين ومساعديهم ومن ينوب عنهم ورؤساء الأقسام في الإدارات العليا في كل من البنوك التجارية الأردنية، وتم جمع البيانات باستخدام أسلوب العينة الهادفة من خلال توزيع الاستبانة على جميع مفردات وحدة المعاينة والبالغ عددهم (216) موظف وموظفة حيث بلغ عدد الاستبانات المستردة والصالحة للتحليل (154) استبانة والتي تشكل استجابة (62%) من الاستبانات الموزعة، تم استخدام اختبارات الإحصاء الوصفي، واختبارات الإحصاء الاستدلالي، وأظهرت النتائج أن المسؤولية المجتمعية بأبعادها (الخيري، الأخلاقي، القانوني، الاقتصادي) لها تأثير دال إحصائيًا في تحسين السمعة التنظيمية في البنوك التجارية الأردنية بأبعادها (الإبداع، جودة الخدمة، الشفافية، جذب المواهب). بناء على النتائج التي تم التوصل إليها توصي الدراسة بضرورة تعزيز المعمارية التنظيمية للبنوك وذلك من خلال نشر الوعي الوظيفي عن طريق تحفيز الموظفين بالالتزام بالقيم التنظيمية وتشجيع العمل الإيجابي والعمل والتفاعل فيما بينهم. The study aimed to identify the impact of social responsibility on improving organizational reputation by the existence of the organizational architecture as a moderator variable at the Jordanians commercial banks. The study population consisted of managers, their assistants, their representatives, and heads of departments in the higher managements of each of the Jordanian commercial banks. The data was collected using the purposeful sampling method by distributing the questionnaire to all the items of the sampling unit, which numbered (216) male and female employees. Where the number of questionnaires retrieved and valid for analysis reached (154), which constitutes a response rate (62%) of the distributed questionnaires. Descriptive statistics tests and inferential statistics tests were used. The results showed that social responsibility with its dimensions (philanthropic, moral, legal, economic) has a statistically significant effect in improving the regulatory reputation in Jordanian commercial banks with its dimensions: (creativity, quality of service, transparency, attracting talents). Based on the findings, the study recommends the need to strengthen the organizational architecture of banks by spreading job awareness by motivating employees to adhere to organizational values and encouraging positive work, work and interaction among them.
Keywords: البنوك التجارية -- المسؤولية الاجتماعية -- الثقافة التنظيمية